Odysseys Home : Mapping African-Canadian Literature - Clarke, George Elliott (Heritage, 2017)
Odysseys Home: Mapping African-Canadian Literatureis a pioneering study of African-Canadian literary creativity, laying the groundwork for future scholarly work in the field. Based on extensive excavations of archives and texts, this challenging passage through twelve essays presents a history of the literature and examines its debt to, and synthesis with, oral cultures. George Elliott Clarke identifies African-Canadian literature's distinguishing characteristics, argues for its relevance to both African Diasporic Black and Canadian Studies, and critiques several of its key creators and texts. Scholarly and sophisticated, the survey cites and interprets the works of several major African-Canadian writers, including André Alexis, Dionne Brand, Austin Clarke, Claire Harris, and M. Nourbese Philip. In so doing, Clarke demonstrates that African-Canadian writers and critics explore the tensions that exist between notions of universalism and black nationalism, liberalism and conservatism. These tensions are revealed in the literature in what Clarke argues to be -paradoxically -uniquely Canadianandproudly apart from a mainstream national identity. Clarke has unearthed vital but previously unconsidered authors, and charted the relationship between African-Canadian literature and that of Africa, African America, and the Caribbean. In addition to the essays, Clarke has assembled a seminal and expansive bibliography of texts -literature and criticism -from both English and French Canada. This important resource will inevitably challenge and change future academic consideration of African-Canadian literature and its place in the international literary map of the African Diaspora.